Acoustical studies of some 1,3,4-thiadiazole derivatives in acetone at 303.15 k - Santhi, N.; Alamelumangai, G. (International Journal of Advanced Chemistry, 2014)
Some new 1, 3, 4-thiadiazole have been synthesized and characterized by IR and NMR spectra. Densities, viscosities and ultrasonic velocities of these compounds have been measured over the wide composition range at 303.15 K in acetone. From these data, various acoustical parameters were evaluated. Some these parameters are adiabatic compressibility, intermolecular free length, relaxation strength, relative association, Rao’s molar constant, salvation number etc. The behaviour of solutions of these compounds in acetone is explained from the evaluated parameters.   Keywords: 1, 3, 4-Thiadiazole, density, velocity, Acetone, acoustical properties.